MANAGERIAL ACCOUNTING DECISION MAKING BY UTILIZING ARTIFICIAL INTELLIGENCE FOR PROFIT PLANNING - Dwi Rahmawati, Indriyani; Oktavia, Eni; Abadi, Satria; Irma Tripalupi, Ramadhani (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to evaluate the efficiency of decision-making in managerial accounting by utilizing artificial intelligence (AI) technology in profit planning, primarily through profit volume cost (CVP) analysis. Digitalization raises new questions for decision-making and triggers new practices of organizational decision-making at the managerial level. The qualitative narrative approach is used to conduct an in-depth literature review. The results show that the application of AI in managerial accounting decision-making can improve automation in the collection, processing, and analysis of financial data and convert it into more accurate management information. Thus, the study concluded that using AI in managerial accounting decision-making improves efficiency and allows for cost prediction with a higher degree of accuracy. The implications of these findings point to the importance of integrating AI technology in accounting practices to support better decision-making.